2022
DOI: 10.3389/fimmu.2022.1015224
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of African swine fever virus to porcine kidney cells stably expressing CD163 and Siglec1

Abstract: African swine fever virus (ASFV) is a complex large DNA enveloped virus that causes African swine fever (ASF) with a fatality rate of up to 100%, seriously threatening the global swine industry. Due to the strict cell tropism of ASFV, there is no effective in vitro cell line, which hinders its prevention and control. Herein, we analyzed genome-wide transcriptional profiles of ASFV-susceptible porcine alveolar macrophages (PAMs) and non-susceptible cell lines PK15 and 3D4-21, an found that PAM surface pattern r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…IFN-α-induced activation of STAT1 and IRF1 is responsible for the production of IL-10 by human monocytes/macrophages[23]. However, it was shown that ASFV inhibits the expression of type I IFN in susceptible cells[24,25,26]. Consistent with this data, we also observed low levels of IFN-α in the supernatants of Mφ0 cells exposed to the active virus.…”
supporting
confidence: 89%
“…IFN-α-induced activation of STAT1 and IRF1 is responsible for the production of IL-10 by human monocytes/macrophages[23]. However, it was shown that ASFV inhibits the expression of type I IFN in susceptible cells[24,25,26]. Consistent with this data, we also observed low levels of IFN-α in the supernatants of Mφ0 cells exposed to the active virus.…”
supporting
confidence: 89%
“…However, none of the corresponding peptide motifs within porcine CD163 were capable of binding G. parasuis , indicating different pathogen–host interaction mechanisms among different pathogens. We should not totally exclude certain roles of other peptides within CD163 in mediating infection, especially the interaction between CD163 and the virulence factors of G. parasuis , although based on previous reports [ 16 , 18 , 19 , 21 , 22 ] and our investigation, we presume that this possibility is very low.…”
Section: Discussionmentioning
confidence: 68%
“…Research on S. mutans has mapped their bacterial binding site to the CD163p2 and CD163p3 peptide motifs in the second and third SRCR domains of human CD163, respectively [ 16 ]. In pigs, porcine CD163 has also been proved to be the key receptor of ASFV [ 18 ] and PRRSV [ 19 ]. When lacking the CD163 SRCR5 domain, porcine alveolar macrophages isolated from genome-edited pigs were fully resistant to PRRSV; thus, their normal biological function is just as important [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations